ESSENTIAL ELEMENTS OF TAXATION - INVESTMENT PROTECTION AND DISPUTE SETTLEMENT - Castagna, Stefano (Elgar Arbitration Law and Practice series, 2021)
When matters of investment and international operations are intertwined with elements of taxation, thorny issues tend to present themselves at the practitioner's doorstep. Investment arbitration is sufficiently complex by itself, as are international tax arbitration cases. The reciprocal impact and potential interactions between international investment arbitration and international taxation is a topic where one must humbly1 acknowledge that there will never be a hard drive large enough to store all solutions to all issues that might arise.2 It might be difficult even for the best practitioner to anticipate how the tax liability in relation to the damages awarded to a claimant by an investment tribunal will be treated by the jurisdictions involved, or how a tax administration will address the taxation of a given operation between multiple related entities. One should therefore be particularly careful in managing risk. On the other hand, investment tribunals have struggled to juggle maintaining equilibrium between the rights of claimants and respondents in various instances, including tax audits and indirect expropriation cases. It is striking, however, that only in the recent past has academia begun to recognize the importance of knowing the main aspects of and interplay between taxation and investment arbitration. Relevant sums of money are at stake when taxation issues are argued in investment cases, and there is much that the dispute settlement regimes of both specialties of law may benefit from considering the best practices adopted by the other. This chapter will focus first on providing an introduction to the most relevant issues that could arise in relation to tax and international investment, giving particular weight to investment protection standards. It will then turn to consider international tax dispute resolution, and thirdly how the particular characteristics of this latter regime may be helpful in the context of the international investment arena.